Multiple streams and policy ambiguity - DeLeo, Rob A.; Zohlnhöfer, Reimut; Zahariadis, Nikolaos (Cambridge elements. Elements in public policy, 2024)
The last decade has seen a proliferation of research bolstering the theoretical and methodological rigor of the Multiple Streams Framework (MSF), one of the most prolific theories of agenda-setting and policy change. This Element sets out to address some of the most prominent criticisms of the theory, including the lack of empirical research and the inconsistent operationalization of key concepts, by developing the first comprehensive guide for conducting MSF research. It begins by introducing the MSF, including key theoretical constructs and hypotheses. It then presents the most important theoretical extensions of the framework and articulates a series of best practices for operationalizing, measuring, and analyzing MSF concepts. It closes by exploring existing gaps in MSF research and articulating fruitful areas of future research.